2006
DOI: 10.1111/j.1442-200x.2006.02229.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical treatment of molluscum contagiosum with imiquimod 5% cream in Turkish children

Abstract: When all the patients affected with MC who exclusively used IQ 5% cream as mentioned in the literature were studied, 35 of 83 patients (42.2%) had complete clearance. These have differences in the form and duration of application. IQ 5% cream can be preferred in the treatment of children with MC because of its applicability at home, easy application and good tolerability. However, different application methods and suitable treatment methods should be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Studies evaluating the effectiveness and clearance rates of IMQ for molluscum range between 33% and 77% for complete clearance, and comparable numbers for partial clearance rates when applied 3–5 times a week for 12 weeks (7,21,22). In another open‐label study, 13 healthy children having MC treated with IMQ, 33% showed complete clearance at the end of 4 weeks of treatment (23).…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the effectiveness and clearance rates of IMQ for molluscum range between 33% and 77% for complete clearance, and comparable numbers for partial clearance rates when applied 3–5 times a week for 12 weeks (7,21,22). In another open‐label study, 13 healthy children having MC treated with IMQ, 33% showed complete clearance at the end of 4 weeks of treatment (23).…”
Section: Discussionmentioning
confidence: 99%
“…Destructive measures include curettage, cryotherapy, needle pricking, and topical vesicants such as cantharidin (2,3). Other destructive approaches include retinoids, silver nitrate, potassium hydroxide, salicylic acid, and phenols (4–14). Immunologic therapies include imiquimod, nitric oxide, and cimetidine, although the efficacy of these therapies remains controversial.…”
mentioning
confidence: 99%
“…Apart from many ongoing trials, Food and Drug Administration approved TLR ligands, MPLA (TLR4 agonist), and imiquimod (TLR7 agonist) could be highlighted to address adjuvant or drug roles. MPLA has been used in various vaccine formulations, for instance, Fendrix (Hepatitis B vaccine, GSK), as an adjuvant and imiquimod is famously used to cure viral diseases as a drug . The majority of TLRs produce redundant responses (inflammatory vs antiviral); however, there are slight, but distinct, differences in outcomes .…”
Section: Tlr Ligands: Adjuvants Vs Drugsmentioning
confidence: 99%